The impact of the social construct of race on outcomes among bacille Calmette‐Guérin‐treated patients with high‐risk non‐muscle–invasive bladder cancer in an equal‐access setting. Issue 21 (8th July 2021) - Lawler, Corinne; Gu, Lin; Howard, Lauren E.; Branche, Brandee; Wiggins, Emily; Srinivasan, Aditya; Foster, Meagan L.; Klaassen, Zachary; De Hoedt, Amanda M.; Gingrich, Jeffrey R.; Theodorescu, Dan; Freedland, Stephen J.; et al.
Abstract : Background: The objective of this study was to describe bladder cancer outcomes as a function of race among patients with high‐risk non–muscle‐invasive bladder cancer (NMIBC) in an equal‐access setting. Methods: A total of 412 patients with high‐risk NMIBC who received bacille Calmette‐Guérin (BCG) from January 1, 2010, to December 31, 2015, were assessed. The authors used the Kaplan‐Meier method to estimate event‐free survival and Cox regression to determine the association between race and recurrence, progression, disease‐specific, and overall survival outcomes. Results: A total of 372 patients who had complete data were included in the analysis; 48 (13%) and 324 (87%) were Black and White, respectively. There was no difference in age, sex, smoking status, or Charlson Comorbidity Index by race. White patients had a higher socioeconomic status with a greater percentage of patients living above the poverty level in comparison with Black patients (median, 85% vs 77%; P < .001). A total of 360 patients (97%) received adequate induction BCG, and 145 patients (39%) received adequate maintenance BCG therapy. There was no significant difference in rates of adequate induction or maintenance BCG therapy according to race. There was no significant difference in recurrence (hazard ratio [HR], 1.53; 95% confidence interval [CI], 0.64‐3.63), progression (HR, 0.77; 95% CI, 0.33‐1.82), bladder cancer–specific survival (HR, 1.01; 95% CI, 0.30‐3.46), or overall survival (HR, 0.97; 95% CI, 0.56‐1.66) according to Black race versus White race. Conclusions: In this small study from an equal‐access setting, there was no difference in the receipt of BCG or any differences in bladder cancer outcomes according to race. Abstract : In this population‐based study within the largest equal‐access setting in the United States, among patients with high‐risk non–muscle‐invasive bladder cancer, there is no difference in age, sex, smoking status, or Charlson Comorbidity Index by race. There is no significant difference in rates of adequate induction or maintenance bacille Calmette‐Guérin therapy or any other outcomes measured according to race.